Nullscript inhibits Cryptosporidium and Toxoplasma growth. (December 2020) - Murakoshi, Fumi; Bando, Hironori; Sugi, Tatsuki; Adeyemi, Oluyomi Stephen; Nonaka, Motohiro; Nakaya, Takaaki; Kato, Kentaro
Abstract: Cryptosporidium and Toxoplasma are parasites that have caused problems worldwide. Cryptosporidium causes severe watery diarrhoea and may be fatal in immunocompromised patients and in infants. Nitazoxanide is the only agent currently approved by the FDA, but its efficacy is limited. Toxoplasmosis is also a problem in the immunocompromised, as currently available treatment options have limited efficacy and patient tolerance can be poor. In the present investigation, we screened libraries of epigenetic compounds to identify those that inhibited C. parvum growth. Nullscript was identified as a compound with an inhibitory effect on C. parvum and T. gondii growth, and was less toxic to host cells. Nullscript was also able to significantly decrease oocyst excretion in C. parvum -infected SCID mice. Graphical abstract: Image 1 Highlights: A library of epigenetic compounds was used to screen for compounds effective against Cryptosporiium parvum . Nullscript has been shown to be effective in inhibiting the growth of  C. parvum  and  T. gondii . Nullscript significantly decreased oocyst excretion in C. parvum -infected SCID mice.